2017
DOI: 10.1002/imhj.21630
|View full text |Cite
|
Sign up to set email alerts
|

Best Practice in Individual Supervision of Psychologists Working in the French Capedp Preventive Perinatal Home-Visiting Program: Results of a Delphi Consensus Process

Abstract: Individual supervision of home-visiting professionals has proved to be a key element for perinatal home-visiting programs. Although studies have been published concerning quality criteria for supervision in North American contexts, little is known about this subject in other national settings. In the context of the CAPEDP program (Compétences parentales et Attachement dans la Petite Enfance: Diminution des risques liés aux troubles de santé mentale et Promotion de la résilience; Parental Skills and Attachment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 13 publications
(15 reference statements)
2
8
0
1
Order By: Relevance
“…Several of the findings from the current study corresponded with prior work investigating the essential components of RS/C from the supervisor's perspective (Greacen et al., 2017; Tomlin et al., 2014). Greacen and colleagues (2017) found that supervisors felt strongly that the provision of RS/C should be regular and organized, confidential, private, and uninterrupted. In addition, supervisors described feeling that their own behaviors such as being fully present were critical to effective RS/C.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…Several of the findings from the current study corresponded with prior work investigating the essential components of RS/C from the supervisor's perspective (Greacen et al., 2017; Tomlin et al., 2014). Greacen and colleagues (2017) found that supervisors felt strongly that the provision of RS/C should be regular and organized, confidential, private, and uninterrupted. In addition, supervisors described feeling that their own behaviors such as being fully present were critical to effective RS/C.…”
Section: Discussionsupporting
confidence: 87%
“…Extending this work, Greacen et al. (2017) implemented the same survey method used by Tomlin et al. (2014) with supervisors ( n = 8) working in a home visiting program and identified four thematic categories of quality supervision : (a) organization and setting of supervision sessions (e.g., confidential; regular; supervisor is not in a hierarchical position regarding the supervisee); (b) supervisor competencies (e.g., has experience working with mother‐child relationships; experience in supervision); (c) relationship between supervisor and supervisor); (e.g., creation of a secure relationship with the supervisee); and (d) supervisor's intervention strategies within supervision (e.g., demonstration of empathy; absence of a judgmental attitude).…”
Section: Introductionsupporting
confidence: 54%
See 3 more Smart Citations